Fifteen-year trend in treatment outcomes among patients with pulmonary smear-positive tuberculosis and its determinants in Arsi Zone, Central Ethiopia - Shallo D. Hamusse; Meaza Demissie; Dejene Teshome; Bernt Lindtjørn (Taylor & Francis Group, 2014)
Background: Directly Observed Treatment Short course (DOTS) strategy is aimed at diagnosing 70% of infectious tuberculosis (TB) and curing 85% of it. Arsi Zone of Ethiopia piloted DOTS strategy in 1992. Since then, the trend in treatment outcomes in general and at district-level in particular has not been assessed. The aim of this study was to analyse the trend in TB treatment outcomes and audit district-level treatment outcomes in the 25 districts of Arsi Zone. Design: A retrospective cohort study design was employed to audit pulmonary smear-positive (PTB + ) patients registered between 1997 and 2011. Demographic and related data were collected from the TB unit registers between January and March 2013. The 15-year trend in treatment outcomes among PTB+ patients and district-level treatment outcomes was computed. Results: From 14,221 evaluated PTB+ cases, 11,888 (83.6%) were successfully treated. The treatment success rate (TSR) varied from 69.3 to 92.5%, defaulter rate from 2.5 to 21.6%, death rate from 1.6 to 11.1%, and failure rate from 0 to 3.6% across the 25 districts of the zone. The trend in TSR increased from 61 to 91% with the increase of population DOTS coverage from 18 to 70%. There was a declining trend in defaulter rate from 29.9 to 2.1% and death rate from 8.8 to 5.4% over 15 years. Patients aged 25-49 years (Adjusted Odd Ratio (AOR), 0.23; 95% CI: 0.21-0.26) and ≥50 years (AOR, 0.43; 95% CI: 0.32-0.59), re-treatment cases (AOR, 0.61; 0.41, 0.67), and TB/HIV co-infection cases (AOR, 0.45; 95% CI: 0.31-0.53) were associated with unsuccessful treatment outcomes. Conclusions: DOTS expansion and improving population DOTS coverage in Arsi has led to a significant increase in treatment success and decrease in death and defaulter rates. However, there is a major variation in treatment outcomes across the 25 districts of the zone, so district-specific intervention strategy needs to be considered. The low TSR among re-treatment cases might be due to the high rate of MDR-TB among this group, and the issue needs to be further investigated to identify the extent of the problem.